Organizing Knowledge = Organizing Data: Applying Principles of Information Organization to the Research Process - Given, Lisa M.; Olson, Hope A. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Organizing research data for effective analysis has been insufficiently addressed in the methodological literature. This paper proposes that principles of knowledge organization relating to relevance, precision, recall, exhaustivity and specificity offer a ready-made model that can be applied to research data. The primary example is drawn from qualitative research to demonstrate how the model can be reinterpreted for that context. Reference is also made to the model's transferability to quantitative and textual research.